Variable structure control with integral action - Ramirez, J.; Bastidas, J.; Vinante, C. (Rev. Téc. Fac. Ing. Univ. Zulia)
Variable structure system control is a rapidly developing no-linear controller design method. It provides attractive features such as fast response and insensitivity to variation in plant parameters. In this work a new reaching law with constant plus integral rate is used to design a variable structure con trolled. This controller was experimentally tested in the digital position control of a DC servomotor. The addition of integral rate to the reaching law. with the proper selection of its parameters. improves the tracking accuracy and the robustness of the variable structure controller.